Technology Innovation as a Driver of Competitive Advantage in Business and Accounting Integration - Ismail Amrani (Journal of Business Innovation and Accounting Research, 2024)
This study investigates the role of technology innovation as a driver of competitive advantage within the context of business and accounting integration in Algeria. As organizations in emerging markets face increasing competitive pressures and technological disruptions, understanding the mechanisms through which technology innovation enhances competitive positioning becomes paramount. Employing a quantitative research methodology, this study collected data from 117 companies across diverse business sectors in Algeria, with particular emphasis on firms implementing digital transformation initiatives. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software to examine the hypothesized relationships between technology innovation constructs and competitive advantage outcomes. The findings reveal that technology innovation significantly and positively influences competitive advantage, with digital transformation and innovation capability emerging as critical determinants. Furthermore, the integration of accounting information systems with business processes demonstrates substantial explanatory power in enhancing organizational performance. The structural model confirms high predictive relevance, with innovation serving as both a direct contributor and mediating mechanism in the relationship between technological adoption and competitive positioning. These results underscore the strategic importance of technology innovation for Algerian enterprises seeking sustainable competitive advantage in an increasingly digitalized business environment.